Comparative study of cyclic voltammetry and cycle stability of electropolymerized poly (3,4-ethylenedioxythiophene) poly(sodium 4-styrenesulfonate) on screen-printed carbon and platinum electrodes in aqueous media - Benoudjit, Abdel Mohsen; Shohibuddin, Ihda Uswatun Shalihah; Tumian, Afidalina; Wan Salim, Wan Wardatul Amani (Mattingley Publishing Co., Inc., 2020)
Poly (3,4-ethylenedioxythiophene) poly(sodium 4-styrenesulfonate) (PEDOT:PSS) electropolymerized and deposited onto screen-printed carbon electrodes (SPCEs) and screen-printed platinum electrodes (SPPEs) was studied for anodic/cathodic peak current and cycle stability. Cyclic voltammetry (CV) shows that the redox ability of SPCEs electropolymerized with PEDOT:PSS (PEDOT:PSS/SPCEs) was significantly improved in comparison to SPPEs electropolymerized with PEDOT:PSS (PEDOT:PSS/SPPEs; the peak current difference of oxidation and reduction (ΔI) for PEDOT:PSS/SPCEs was ~3 times higher than that of PEDOT:PSS/SPPEs (ΔISPCE = 350 µA, ΔISPPE = 125 µA). Oxidation and reduction peak current of the CVs showed that both electrodes could maintain electrode integrity for over 30 days. The results suggest that the electropolymerized PEDOT:PSS had good adhesion to SPCE and SPPE surfaces. There was an insignificant change in the cycle stability curve after 3000 cycles compare to the initial cycle (p-value = 0.5) and an insignificant change in the cycle stability curve after 30 days in comparison to the first day (p-value = 0.9). The results suggest that electrode integrity of both PEDOT:PSS/SPCEs and PEDOT:PSS/SPPEs were maintained after repetitive CV cycles in aqueous media.